Electron transport phosphorylation in rumen butyrivibrios: unprecedented ATP yield for glucose fermentation to butyrate - Hackmann, Timothy J.; Firkins, Jeffrey L. (Frontiers in Microbiology, 2015)
From a genomic analysis of rumen butyrivibrios (Butyrivibrio and Pseudobutyrivibrio spp.), we have re-evaluated the contribution of electron transport phosphorylation to ATP formation in this group. This group is unique in that most (76%) genomes were predicted to possess genes for both Ech and Rnf transmembrane ion pumps. These pumps act in concert with the NifJ and Bcd-Etf to form a electrochemical potential (ΔμH+ and ΔμNa+), which drives ATP synthesis by electron transport phosphorylation. Of the 62 total butyrivibrio genomes currently available from the Hungate 1000 project, all 62 were predicted to possess NifJ, which reduces oxidized ferredoxin (Fdox) during pyruvate conversion to acetyl-CoA. All 62 possessed all subunits of Bcd-Etf, which reduces Fdox and oxidizes reduced NAD (NADred) during crotonyl-CoA reduction. Additionally, 61 genomes possessed all subunits of the Rnf, which generates ΔμH+ or ΔμNa+ from oxidation of reduced Fd and reduction of oxidized NAD (NADox). Further, 47 genomes possessed all 6 subunits of the Ech, which generates ΔμH+ from oxidation of reduced Fd (Fdred). For glucose fermentation to butyrate and H2, the electrochemical potential established should drive synthesis of ~1.5 ATP by the F0F1-ATP synthase (possessed by all 62 genomes). The total yield is ~4.5 ATP/glucose after accounting for 3 ATP formed by classic substrate-level phosphorylation, and it is one the highest yields for any glucose fermentation. The yield was the same when unsaturated fatty acid bonds, not H+, served as the electron acceptor (as during biohydrogenation). Possession of both Ech and Rnf had been previously documented in only a few sulfate-reducers, was rare in other rumen prokaryotic genomes in our analysis, and may confer an energetic advantage to rumen butyrivibrios. This unique energy conservation system might enhance the butyrivibrios’ ability to overcome growth inhibition by unsaturated fatty acids, as postulated herein.